Ultra-fast vitrification of patient-derived circulating tumor cell lines. - Rebecca D Sandlin; Keith H K Wong; Shannon N Tessier; Anisa Swei; Lauren D Bookstaver; Bennett E Ahearn; Shyamala Maheswaran; Daniel A Haber; Shannon L Stott; Mehmet Toner (PLoS ONE, 2018)
Emerging technologies have enabled the isolation and characterization of rare circulating tumor cells (CTCs) from the blood of metastatic cancer patients. CTCs represent a non-invasive opportunity to gain information regarding the primary tumor and recent reports suggest CTCs have value as an indicator of disease status. CTCs are fragile and difficult to expand in vitro, so typically molecular characterization must be performed immediately following isolation. To ease experimental timelines and enable biobanking, cryopreservation methods are needed. However, extensive cellular heterogeneity and the rarity of CTCs complicates the optimization of cryopreservation methods based upon cell type, necessitating a standardized protocol. Here, we optimized a previously reported vitrification protocol to preserve patient-derived CTC cell lines using highly conductive silica microcapillaries to achieve ultra-fast cooling rates with low cryoprotectant concentrations. Using this vitrification protocol, five CTC cell lines were cooled to cryogenic temperatures. Thawed CTCs exhibited high cell viability and expanded under in vitro cell culture conditions. EpCAM biomarker expression was maintained for each CTC cell line. One CTC cell line was selected for molecular characterization, revealing that RNA integrity was maintained after storage. A qPCR panel showed no significant difference in thawed CTCs compared to fresh controls. The data presented here suggests vitrification may enable the standardization of cryopreservation methods for CTCs.